Content validation in concepts of management and managerial practices in Nursing - Abel Silva de Meneses; Isabel Cristina Kowal Olm Cunha (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to define and validate 37 concepts emanating from the epistemology of knowledge about Nursing Administration. Methods: theoretical-methodological study using the Delphi technique in 37 concepts and definitions built on the knowledge of more than half a century of research on Nursing Administration. The concepts were submitted to the judgment of a panel of 21 judges and the validation was measured by the content validity index (> 0.78) and Kappa coefficient (> 0.61). Results: enunciation of 37 concepts and definitions capable of reflecting the knowledge about Nursing Administration. The 37 concepts were validated by the judges, resulting in content validity indices that ranged from 0.81 to 1.00, with reliability higher than 0.79. Conclusions: the epistemological solution presented was validated by the judges with indices above 0.80 and high reliability of universal agreement, constituting a new object of ontological understanding for the scientific nursing community.